2012
DOI: 10.1155/2012/151967
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Dengue Rapid Diagnostic Tests for Point-of-Care Application: Recent Evaluations and Future Needs?

Abstract: Dengue fever, dengue haemorrhagic fever, and dengue shock syndrome (DF/DHF/DSS) are tropical diseases that cause significant humanitarian and economic hardship. It is estimated that more than 2.5 billion people are at risk of infection and more than 100 countries have endemic dengue virus transmission. Laboratory tests are essential to provide an accurate diagnosis of dengue virus infection so that appropriate treatment and patient management may be administered. In many dengue endemic settings, labora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
113
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(119 citation statements)
references
References 49 publications
4
113
0
2
Order By: Relevance
“…Los tests inmunocromatográficos son ampliamente utilizados en nuestro país para el diagnóstico de la infección por DENV, tanto en centros asistenciales del sector público como en laboratorios privados. Si bien el fabricante reporta una elevada sensibilidad (92,8%) y especificidad del 98.4%), estudios como el de Tricou et al (2010) reportan una sensibilidad del 80,3% para una infección primaria por DENV, mientras que la sensibilidad decae a un 56,3% en los casos de infecciones secundarias para el test inmunocromatográfico empleado en este estudio (14), mientras que Blacksell et al (2012) reportan sensibilidades variadas de acuerdo a diversas marcas de tests inmunocromatográficos que van del 99 al 10% (15).…”
Section: Discussionunclassified
“…Los tests inmunocromatográficos son ampliamente utilizados en nuestro país para el diagnóstico de la infección por DENV, tanto en centros asistenciales del sector público como en laboratorios privados. Si bien el fabricante reporta una elevada sensibilidad (92,8%) y especificidad del 98.4%), estudios como el de Tricou et al (2010) reportan una sensibilidad del 80,3% para una infección primaria por DENV, mientras que la sensibilidad decae a un 56,3% en los casos de infecciones secundarias para el test inmunocromatográfico empleado en este estudio (14), mientras que Blacksell et al (2012) reportan sensibilidades variadas de acuerdo a diversas marcas de tests inmunocromatográficos que van del 99 al 10% (15).…”
Section: Discussionunclassified
“…However NSI research is not recommended in places with endemic dengue where late clinical manifestations may occur. The test is effective in such places when combined with IgM research (BLACKSELL, 2012). A low-cost alternative with an easy installation in emergency services is the fast immunochromatography dengue test.…”
Section: Discussionmentioning
confidence: 99%
“…[2] Simple and rapid ICT with the detection of NS1 antigen, IgM/IgG antibodies provide opportunities for point-of-care diagnosis especially in many dengue endemic settings, where laboratory diagnostic resources are limited. [4] Previous studies across the world have reported gender related differences in serological and haematological findings of dengue infection. [5][6] However, data regarding this aspect of dengue fever is lacking in Indian settings especially in Central part of India where dengue is endemic.…”
Section: Introductionmentioning
confidence: 99%